2021
DOI: 10.1016/j.aohep.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Aminotransferases disorders associated with venous thromboembolic events in patients infected with COVID-19

Abstract: Introduction and objectives Since the outbreak of the COVID-19 pandemic, increasing evidence suggests that infected patients present a high incidence of venous thromboembolic (VTE) events and elevated aminotransferases (AT).The objective of this work was to evaluate the incidence of aminotransferases disorders in patients infected with COVID-19 and to manage the VTE events associated with elevated AT. Patients or Materials and methods We report a retrospective study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The probable reason for the low detection rate of thrombosis in our study population was that lower extremity ultrasound was not performed routinely in all our patients, but only for those with clinical signs of thrombosis or a significant increase in D-dimer. On the other hand, Hamadé et al, 20 studied only 46 patients against our 828, giving our results greater statistical power.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The probable reason for the low detection rate of thrombosis in our study population was that lower extremity ultrasound was not performed routinely in all our patients, but only for those with clinical signs of thrombosis or a significant increase in D-dimer. On the other hand, Hamadé et al, 20 studied only 46 patients against our 828, giving our results greater statistical power.…”
Section: Discussionmentioning
confidence: 61%
“…The possible relationship between hypercoagulation and hypertransaminasemia is discussed in the work of Hamadé et al, 20 which retrospectively shows a potential association between elevated transaminases and venous thrombosis. Our study found no similar associations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Amer and his colleagues published an interesting study entitled “Aminotransferases disorders associated with venous thromboembolic events in patients infected with COVID-19” in Annals of Hepatology [ 1 ]. In this retrospective study, the authors explored the association between venous thromboembolic (VTE) events and elevated aminotransferases (AT) in patients infected with COVID-19.…”
mentioning
confidence: 99%
“…Zhu et al published an interesting correspondence [1] regarding the article we published in October 2020 in Annals of Hepatology [2] .…”
mentioning
confidence: 99%